Perkutana balonska dilatacija aortne zaklopke - Ambrožič, Jana (Zdravniški vestnik, 2010)
Background: As the population ages there is an increasing number of elderly patients with severe symptomatic aortic stenosis and numerous co-morbidities. Decision for aortic valve replacement-a gold standard for the treatment of aortic stenosis-might be difficult in this group of patients,in whom open heart procedure may be associated with an unacceptably high risk. Less invasive percutaneous methods are being developed as alternative options for improving the quality of life and prolonging survival. Balloon aortic valvuloplasty is a percutaneous catheterbased method for dilation of the aortic valve, which was in the past almost abandoned due to a high incidence of restenosis and the lack of impact on long-term survival. Twenty years aft er its introduction in the elderly patients, together with the development of percutaneous aortic valve implantation methods, balloon aortic valvuloplasty is regaining its role. Case report: We report a case of a 88-yearold woman with severe symptomatic aortic stenosis and a high perioperative risk, who wasconsidered unsuitable for surgical aortic valve replacement. Owing to worsening of her symptoms, she had balloon aortic valvuloplasty performed. After the procedure she improved clinically and objectively. Conclusions: Our case points out that there are additional therapeutic options for highrisk patients with severe aortic stenosis. Many share the opinion that balloon aortic valvuloplasty will play an important role as a palliative therapy or a bridge to surgical or percutaneous prosthetic valve implantation.
Keywords: Aged, 80 And Over; aorta; Aortic Valve Stenosis; Aortna zaklopka, stenoza; Balloon Dilatation; Balonska dilatacija; cardiovascular disease; Echocardiography, Doppler; Ehokardiografija dopplerska; kardiovaskularne bolezni; kirurško zdravljenje; Starost 80 in več; stenoza; Therapy; Treatment Outcome; zaklopke; Zdravljenje, izid